Menuju Profil Pancasila Siswa: Implementasi Pendidikan Multikultural dalam Membentuk Karakter Toleransi dan Gotong Royong pada Pembelajaran Ilmu Pengetahuan Alam dan Ilmu Pengetahuan Sosial di Sekolah Dasar - Silfi Melindawati; E. Kus Eddy Sartono; Wuri Wuryandani; Fatia Fatimah (Postgraduate, University of Mataram, 2024)
This research aims to develop and implement a multicultural education program in Science and Social learning in elementary schools to shape students' characters according to the learner profile of Pancasila, especially in terms of tolerance and mutual cooperation. The ADDIE (Analysis, Design, Development, Implementation, and Evaluation) approach was used in designing this program. The results showed a significant increase in students' understanding of the values of tolerance and mutual cooperation, as seen from the comparison of pre-test and post-test scores. Students showed a more active and open attitude towards differences, while teachers felt the program helped enrich learning. The evaluation also indicated that the program needs to be adapted for different abilities of students. In conclusion, this multicultural education program proved to be effective in shaping character according to the values of Pancasila and deserves to be implemented more widely.